The quality of the KombiFiD-sample of business services enterprises: Evidence from a replication study - Alexander Vogel; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This study tests whether the KombiFiD sample can be regarded as a high quality data set for empirical research on enterprises from business services industries. It performs an empirical investigation using the original data in a first step and replicates exactly this investigation using the KombiFiD sample in a second step. We find that large business services firms are oversampled in the KombiFiD agreement sample which leads to a higher share of exporting business services firms compared to the original data. After controlling for firm size and industries results based on the original data and on the KombiFiD sample are highly similar for West German firms. Therefore, the KombiFiD sample can be regarded as a sound base for empirical studies on West German firms from business services industries. For East Germany, however, the number of business services firms seems to be too small for empirical analyses, at least in the field of firm's export participation.
Keywords: C81; 330; KombiFiD; Germany; business services firms; Unternehmensdienstleistung; Statistik der Unternehmen und Arbeitsstätten; Stichprobenverfahren; Deutschland